Word Wins Over Face: Emotional Stroop Effect Activates the Frontal Cortical Network - Ovaysikia, Shima; Chan, Jason L.; Tahir, Khalid; DeSouza, Joseph F. (Frontiers in Human Neuroscience, 2011)
The prefrontal cortex (PFC) has been implicated in higher order cognitive control of behaviour. Sometimes such control is executed through suppression of an unwanted response in order to avoid conflict. Conflict occurs when two simultaneously competing processes lead to different behavioral outcomes, as seen in tasks such as the anti-saccade, go/no-go and the Stroop task. We set out to examine whether different types of stimuli in a modified emotional Stroop task would cause similar interference effects as the original Stroop-colour/word, and whether the required suppression mechanism(s) would recruit similar regions of the medial PFC (mPFC). By using emotional words and emotional faces in this Stroop experiment, we examined the two well-learned automatic behaviours of word reading and recognition of face expressions. In our emotional Stroop paradigm, words were processed faster than face expressions with incongruent trials yielding longer reaction times (RT) and larger number of errors compared to the congruent trials. This novel Stroop effect activated the anterior and inferior regions of the mPFC, namely the anterior cingulate cortex (ACC), inferior frontal gyrus (IFG) as well as the superior frontal gyrus. Our results suggest that prepotent behaviours such as reading and recognition of face expressions are stimulus-dependent and perhaps hierarchical, hence recruiting distinct regions of the mPFC. Moreover, the faster processing of word reading compared to reporting face expressions is indicative of the formation of stronger stimulus-response (SR) associations of an over-learned behaviour compared to an instinctive one, which could alternatively be explained through the distinction between awareness and selective attention.